Robotically-Assisted Coronary Artery Bypass Grafting - Thierry A. Folliguet; Alain Dibie; François Philippe; Fabrice Larrazet; Michel S. Slama; François Laborde (Cardiology Research and Practice)
Objectives. Robotic surgery enables to perform coronary surgery totally endoscopically. This report describes our experience using the da Vinci system for coronary artery bypass surgery. Methods. Patients requiring single-or-double vessel revascularization were eligible. The procedure was performed without cardiopulmonary bypass on a beating heart. Results. From April 2004 to May 2008, fifty-six patients were enrolled in the study. Twenty-four patients underwent robotic harvesting of the mammary conduit followed by minimal invasive direct coronary artery bypass (MIDCAB), and twenty-three patients had a totally endoscopic coronary artery bypass (TECAB) grafting. Nine patients (16%) were converted to open techniques. The mean total operating time for TECAB was 372±104 minutes and for MIDCAB was 220±69 minutes. Followup was complete for all patients up to one year. There was one hospital death following MIDCAB and two deaths at follow up. Forty-eight patients had an angiogram or CT scan revealing occlusion or anastomotic stenoses (>50%) in 6 patients. Overall permeability was 92%. Conclusions. Robotic surgery can be performed with promising results.